2020
DOI: 10.1111/odi.13506
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of SIX1, ME2, and AP2M1 in adenoid cystic carcinoma and mucoepidermoid carcinoma

Abstract: Objective: Adenoid cystic carcinoma (AdCC) and mucoepidermoid carcinoma (MEC) are the most frequent malignancies in the salivary glands. The purpose of this study was to explore the roles of sine oculis homeobox homolog 1 (SIX1), malic enzyme 2 (ME2), and AP-2 complex subunit mu (AP2M1) in AdCC and MEC, as well as the potential relationship between SIX1, ME2, AP2M1, and proliferation marker cyclin D1. Material and methods: Immunohistochemistry was performed on human salivary gland tissue microarrays that conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…A new study indicates that RPS6KA1 is a potential target of new treatment strategies for drug-resistant AML patients with FLT3-ITD mutation, especially combining PI3K, PIM, or Bcl-2 family members (Watanabe et al, 2019). As for AP2M1, its role in gallbladder cancer, mucoepidermoid carcinoma, liver cancer, and adenoid cystic carcinoma was generally clear (Cho et al, 2019;Song et al, 2020;Wu et al, 2020), but it is seldom reported how AP2M1 is involved in AML progression.…”
Section: Discussionmentioning
confidence: 99%
“…A new study indicates that RPS6KA1 is a potential target of new treatment strategies for drug-resistant AML patients with FLT3-ITD mutation, especially combining PI3K, PIM, or Bcl-2 family members (Watanabe et al, 2019). As for AP2M1, its role in gallbladder cancer, mucoepidermoid carcinoma, liver cancer, and adenoid cystic carcinoma was generally clear (Cho et al, 2019;Song et al, 2020;Wu et al, 2020), but it is seldom reported how AP2M1 is involved in AML progression.…”
Section: Discussionmentioning
confidence: 99%
“…Further, following apoptosis induction, AP2M1 expression varies in different types of cells. In addition, AP2M1 is positively associated with cyclin D1 in adenoid cystic carcinoma (AdCC) and mucoepidermoid carcinoma (MEC), indicating that AP2M1 are involved in the proliferation of AdCC and MEC to cause tumor growth [ 18 ]. In the present study, we found that AP2M1 not only regulated the expression of autophagy-related markers, such as Beclin 1, LC3 and p62, but also modulated the expression of apoptosis-related markers bcl-2, bax and cleaved caspase3.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AP2M1 has been found to be associated with several types of cancer. Cong-Cong Wu et al demonstrated that the expression of AP2M1 was significantly elevated in adenoid cystic carcinoma and mucoepidermoid carcinoma, and its expression was closely correlated with the expression of the proliferation marker, cyclin D1 [18]. AP2M1 can also serve as a prognostic marker of hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…demonstrated that the expression of AP2M1 was signi cantly elevated in adenoid cystic carcinoma and mucoepidermoid carcinoma, and its expression was closely correlated with the expression of the proliferation marker, cyclin D1 [18]. AP2M1 can also serve as a prognostic marker of hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 98%